René Magritte - Defeyt, Catherine; Vandepitte, Francisca (Artist's materials., 2023)
"The first comprehensive study of René Magritte's methods and techniques and the eleventh book in the Artist's Materials series, which explores the unique and unconventional materials used by contemporary artists and the challenges encountered by professionals tasked with conserving their works"--